Pengaruh Permainan Papercraft Terhadap Kreativitas pada Anak Usia Dini - Qurrota A'yunin; Padilah (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2023)
For children, playing is one of the fun and exciting activities. Because playing can develop children's creativity. One of them is the papercraft game, which is an art where you combine several origami papers into real 3D. How to make this papercraft by cutting, folding, and also sticking an origami paper. This study aims to determine the effect of papercraft games on creativity in children aged 5-6 years at Asmaul Husna Islamic Kindergarten. The method used by the researcher is Pre-Experimental Design, with the type of One-Group Pretest-Posttest Disgn. Determination of the sample in this study using the purposive sampling technique, because the sample used was in accordance with the needs. The sample used in this study amounted to 13 children. Data collection techniques in this study used observation of treatment to determine the results given. The results of the t-test calculation using a significant level (α) 0.05 and n=13-1=12 obtained t_hitung=10,174 and t_table=1,78. Therefore, it can be concluded that t_hitung>t_tabel or 16.11>1.78 which means H_O is rejected and H_a is accepted. This means that the hypothesis which states that papercraft games have an optimal effect on the creativity of children aged 5-6 years in Asmaul Husna Islamic Kindergarten.